Digital inputs and industrial green transformation: perspectives on intra-industry impacts and inter-industry spillover effects - Li, Guanghao; Lin, Dong (Frontiers in Environmental Science, 2025)
Digital transformation plays an important role in promoting green development. As a key tool for digital transformation, the intra-industry impacts and inter-industry spillover effects of digital inputs on industrial green transformation are topics worthy of further study. Based on a unique Chinese enterprise panel data set, this paper employs a high-dimensional fixed effects model to empirically analyze both the intra-industry impacts and the inter-industry spillovers effect of digital inputs on industrial green transformation. The results show that, digital inputs exert a significant intra-industry impact, it can effectively drive industrial enterprises to achieve green transformation, and this driving effect exhibits heterogeneity across different enterprise sizes, ownership structures, and pollution emission intensities. At the same time, enterprise entry and enterprise exit are the mechanisms that generate intra-industry impacts, digital inputs are conducive to the entry of new enterprises with high efficiency and low pollution into the market, and force inefficient and highly polluting enterprises to exit the market, thereby effectively optimizing the market structure and promoting the green transformation within the industry. In terms of inter-industry spillover effects, there are obvious differences between forward and backward inter-industry spillover effects of digital inputs driving industrial green transformation. It cannot effectively promote the green transformation of downstream related industries through a “supply-led” approach, but it can spillover the promotional effect of digital inputs on green transformation to upstream industries through a “demand-driven” approach. The mechanism analysis results of the inter-industry spillover effects further show that, in a “demand-driven” scenario, capital renewal and technological progress in upstream related industries are the key mechanisms for realizing the inter-industry spillover effects of digital inputs on industrial green transformation. These conclusions provide empirical evidence and policy references for developing countries to use digital inputs for reducing industrial pollution emissions and promoting industrial green transformation.